'Newly qualified general nurses experiences of pre-registration internship: A Republic of Ireland cross-sectional study' - Mooney, Mary; O'Brien, Frances (My University, 2025)
Newly qualified general nurses’ experiences of pre-registration internship: A Republic of Ireland cross-sectional study Background: Nursing Internship was introduced in Ireland in 2002. It and comprises the final 36 weeks of the undergraduate nursing degree programme. The aim of internship was to provide nursing students with clinical experience at an independent level under the distant supervision of a registered nurse (RN) to prepare them for transition to the role of RN.) Aim & objectives: The aim of this study was to examine Newly Qualified General Nurses’ (NQGNs’) experiences and the value of the internship period. Methods: This cross-sectional, quantitative, descriptive Irish study included NQGNs who graduated from Higher Education Institutes in the Republic of Ireland between 2018 and 2020. The anonymous on-line survey was administered using SurveyMonkey. The instrument used was the experience of internship questionnaire. Data were collected nationally and 193 nurses responded to the questionnaire. Data were analysed using the Statistical Package for the Social Sciences (SPSSv 27). This study was approved by Trinity College Dublin School of Nursing & Midwifery Research Ethics Committee [COM_01–18.19]. Findings: Pre-internship preparation varied across sites, with some respondents reporting no preparation for the transition from supernumerary student to intern. Almost all participants concurred with the statement that internship “consolidated their learning and helped them to link theory to practice more than any of their supernumerary placements". There was also greater emphasis on setting and achieving goals during internship. Conclusion and impact: This study examined NQGNs’ experiences of internship and its value in preparing them for practice as an RN. Some reported receipt of preparation for internship and others received none. A national standardised structured approach to preparing supernumerary students for transition to internship is required to maximise student experiences and learning. Internship enabled the realisation of the full extent of the nurse’s role and avoided the experience of ‘reality shock’, something that was previously reported by nurse graduates in the literature.
Book of abstracts https://theconf2025.exordo.com/programme
Trinity Health and Education International Research Conference 2025 (THEconf2025) 'Healthcare in times of crisis: adaptive responses and global innovations'
PUBLISHED
Trinity College Dublin
Keywords: Nursing internship; Clinical learning environment in nursing; Nursing; Nursing Education; Education